Opportunities for the Application of Waste-to-Energy (WtW) Technology to Increase the Effectiveness of Waste Management and Mitigate Global Warming in Nganjuk Regency - Purboseno, Sentot; Astuti, Widi (ARRUS Journal of Engineering and Technology, 2024)
Waste-to-Energy (WtE) technology offers an innovative solution to improve sustainable waste management, especially in areas with significant waste management challenges such as Nganjuk Regency. This study explores the opportunities for implementing WtE in Nganjuk to reduce waste volume, reduce greenhouse gas (GHG) emissions, and provide alternative energy sources. By utilizing technologies such as incineration, pyrolysis, and gasification, WtE facilities can convert waste into renewable energy, reduce dependence on landfills, and reduce methane emissions that contribute to global warming. The results show that WtE implementation can generate environmental and economic benefits, including providing energy for local communities and reducing waste management costs. Community education and active participation in recycling and waste sorting programs are also key to the success of WtE implementation. Government policy support and incentives are identified as important factors in facilitating the adoption of this technology. This study provides important insights for the development of sustainable waste management strategies in Nganjuk and can serve as a model for other areas facing similar challenges. The recommendations provided include increasing cooperation between the government, private sector, and communities to maximize the potential of WtE technology in supporting sustainable development and climate change mitigation. Considering the composition of waste which mostly comes from household waste, where 61.5% is organic waste, the right WtE technology is a biodigester